PERTUMBUHAN TANAMAN SENGON BUTO (Enterolobium cyclocrpum Griseb) FASE TINGKATAN SEMAI DENGAN MEDIA OVERBURDEN - Sukariyan Sukariyan; Marjenah Marjenah; Wawan Kustaiwan; Wahjuni Hartati; Garini Widosari (Politeknik Pertanian Negeri Samarinda, 2021)
Plant growth is known as increasing volume of the diameter and height of the plant stem. Overburdenmaterial after coal mining has conditions where the soil structure is damaged, rock fragmentation ismixed and there is no layer of organic matter. The research objective is to determine the suitability ofplant growth in several growing media. The research method is done by planting test in a nursery withplant growth media consisting of top soil material as a control, a mixing of overburden material withfoliar fertilizer from sengon buto plants, and overburden growing media, the three media werecompared. Results of significance were less than 0.05. The growth medium affects the growth ofsengon buto (Enterolobium cyclocarpum Griseb) seedlings.